RELATIONSHIP OF AGE, GENDER, AND RECURRENT ACUTE OTITIS MEDIA WITH CHRONIC SUPPURATIVE OTITIS MEDIA - Hani Safitri; Ismaily Fasyah; Rizka Aries Putranti (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2026)
Chronic suppurative otitis media (CSOM) can cause hearing loss and negatively affect children's growth and development. Many predisposing factors may influence the development of chronic suppurative otitis media. This condition can be prevented through appropriate preventive measures. This study aimed to determine the relationship between age, gender, and a history of recurrent acute otitis media (AOM) and the incidence of CSOM in children. This observational study used a case-control design. The study sample consisted of children aged 6 months to 18 years, selected through consecutive sampling, comprising 51 children with CSOM and 51 children without CSOM. Data were analyzed using the chi-square and Fisher’s exact test. The most common age group was 1-5 years, and the most common gender was female. Age and gender were not significantly associated with OMS (p = 0.227; OR = 1.630 and p = 0.843, OR = 1.082, respectively). In contrast, recurrent AOM was significantly associated with CSOM (p-value = 0.000 (<0.05); OR = 13.143). Thus, a history of recurrent AOM was identified as the most important factor associated with CSOM in this study, conferring a 13-fold higher risk. Keywords: acute otitis media, age, chronic suppurative otitis media, genderDOI 10.35990/mk.v9n2.p137-149